MPPT control design for variable speed wind turbine - Meriem Otmane Rachedi; Mohammed Larbi Saidi; Fayçel Arbaoui (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Variable speed wind turbine systems (VSWT’s) have been in receipt of extensive attention among the various renewable energy systems. The present paper focuses on fuzzy fractional order proportional-integral (FFOPI) control segment for variable speed wind turbine (VSWT) directly driving permanent magnet synchronous generator (PMSG). The main objective of this study is to reach maximum power point tracking (MPPT) through combination of advanced control based on FFOPI control applied to generator side converter (turbine and PMSG). The basic idea of the FFOPI controller is to implement a fuzzy logic controller (FLC) in cascade with Fractional Order Proportional Integral controller (FOPI). A comparative study with FOPI and classical PI control schemes is made. The traditional PI controller cannot deliver a sufficiently great performance for the VSWT. However, the results found that the proposed approach (FFOPI) is more effective and feasible for controlling the permanent magnet synchronous generator to mantain maximum power extraction. The validation of results has been performed through simulation using Matlab/Simulink®.